Pendugaan Jarak Genetik Kelinci (Hyla, Hycole, Hycolex NZW, Rex, dan Satin) Melalui Analisis Morfometrik (ESTIMATION OF RABBIT GENETIC DISTANCE (HYLA, HYCOLE, HYCOLEXNZW, NZW, REX AND SATIN) THROUGH MORPHOMETRIC ANALYSIS) - Brahmantiyo, Bram; Priyono, Priyono; Rosartio, Rian (Jurnal Veteriner; Vol 17 No 2 (2016), 2016)
The observation on morphological body conformation of Hyla (CC), Hycole (FF), HycolexNZW (FN),New Zealand White (NN), Rex (RR), and Satin (SS) were carried out to determine estimation of mahalanobisgenetic distance. This research was held in Ciawi Bogor Livestock Research Institute (Balai PenelitianTernak Ciawi, Bogor) which 95 head of male rabbits were used. Fourteen different body parts measuredwere head (length, width, and height), ear (length and width), chest (depth, girth, and width), scapulalength, ulna length, femur length, tibia length, body length, and hips wide. CC, FF, FN, and NN rabbits hadbigger morphological size than RR and SS rabbits. Mahalanobis genetic distance showed that geneticdistance of FF and SS rabbits was the biggest (4.36). Result of canonical analysis showed that the mostdiscriminate variables were obtained by head width, ear length, ulna length, tibia length, body length, andhips wide for first canonical. The conclusion of this study that Rex and Satin rabbits were have differentgenetic distance with Hyla, Hycole, HycolexNZW and NZW rabbits.
Keywords: rabbit, genetic distance, morphometric